Evaluation of control accuracy for a boundary-coordinating device in a real-time hybrid test - Tian, Yingpeng; Li, Quanwang; Bu, Changcan; Fan, Fenglei; Wang, Tao (Frontiers in Built Environment, 2024)
Multi-axial real-time hybrid simulation (ma-RTHS) utilizes multiple loading devices to realize boundary control with multiple degrees of freedom (MDOF), thus being capable of handling complex dynamic scenarios and multi-dimensional problems. In this paper, a new control technique was developed by using a parallel configuration of double shaking tables to implement shear force and bending moment at the boundary between substructures. The dynamic forces are combined by inertia forces of controlled mass driven by electromagnetic shaking tables. The two shaking tables are packaged as a boundary-coordinating device (BCD). An enhanced three-variable control (ETVC) was proposed to consider the coupling effect between two shaking tables and incorporated with the adaptive time series (ATS) compensator to improve the synchronization of the two shaking tables. The proposed control method was verified by three rounds of hybrid tests on a four-story steel shear frame using different ground motions. Nine criteria were utilized to evaluate the performance of RTHS including both tracking performance and global performance indexes. It was proved that RTHS was successfully implemented, and the boundary forces were well-tracked by the proposed control strategy. Good tracking performance was achieved to prove the effectiveness of the strategy.